Web Application Design for Community Environmental Incident Reporting - Matthaiou, Christos (My University, 2024)
This thesis focuses on the design and development of "EnvironEyes" a web-based application created to facilitate community-driven environmental incident reporting. Aimed at enhancing environmental awareness and improving community safety, the platform allows residents to report incidents efficiently using their internet-enabled devices. The application integrates features that support user-friendly navigation and real-time updates, fostering quick responses from local authorities. Through this initiative, the platform enhances proactive community engagement by making environmental reporting accessible to all, thus contributing to better environmental quality and safety. Analysis of user interactions and feedback highlights the platform's effectiveness in promoting environmental responsibility among residents. This research demonstrates the pivotal role of digital tools in community-based environmental management and provides a framework for future enhancements to increase user engagement and system functionality.
Keywords: Web Application Design; Community Engagement; Environmental Reporting; Incident Management; User Interaction Design